OPTIMISING THE SCHOOL LIBRARY AS A LEARNING RESOURCE IN INCREASING ELEMENTARY SCHOOL STUDENTS' INTEREST IN READING - Asep Saepurokhman; Abdul Wahab Syakhrani; Suhana Sarkawi; Mowafg Masuwd (International Journal of Teaching and Learning, 2025)
School libraries play an important role in supporting the learning process and developing students' literacy, but they are often not optimally utilised. This study uses the literature method. The results show that school library optimisation can be achieved through several key strategies. Firstly, improving the physical quality of the library by creating a child-friendly and visually appealing environment. Secondly, the development of a diverse collection of books in accordance with students' interests and abilities. Third, the integration of library activities with the school curriculum through active collaboration between librarians and teachers. Fourth, the implementation of interactive programmes such as storytelling, book clubs and reading competitions to increase student engagement. Fifth, the utilisation of digital technology to attract digital generation students. Sixth, involving parents and communities in literacy activities to strengthen the reading culture.